Knowledge of Oral Cancer among the Fourth and Fifth Year Dental Students - Maria Radman; Ana Glavina; Ivan Sabol; marinka Mravak-Stipetić (Acta Stomatologica Croatica, 2018)
Background: The literature data show insufficient knowledge and awareness about oral cancer among dental and medical students. Objective: To assess the knowledge of graduating dental students regarding oral cancer and to assess their awareness regarding the prevention and early detection of oral cancer. Also student’s smoking status was examined aimed to investigate their attitude towards smoking as a risk factor for development of oral cancer and to assess the prevalence of smoking among dental students. Subjects and Methods: The study group consisted of 83 students of the fourth and fifth years of dental medicine study who answered the questions written in the original 16-item questionnaire. Results: More than half of the students considered their knowledge to be good, a quarter of them regarded their knowledge as being poor. Almost 16% of students considered their knowledge to be very good, whereas only two students rated their knowledge as ‘excellent’. Students of the fifth year were more likely to be smokers compared to fourth year students (39.5% vs. 22.5%). Higher percentage of non-smokers than smokers had marked ‘stop smoking’ as an important preventive measure (non-smokers 91.2%, smokers 84.3%, p = 0.01). Conclusion: Majority of the students of fourth and fifth year of study rate their knowledge about oral cancer as good. A large number of students of both years considered hairy leukoplakia a potentially malignant disorder. Students non smokers recognize “stop smoking” as an important preventive measure unlike students smokers who show a more realistic attitude towards smoking as a risk factor for oral cancer.